2009
DOI: 10.1016/j.visres.2009.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Location and color biases have different influences on selective attention

Abstract: Are locations or colors more effective cues in biasing attention? We addressed this question with a visual search task that featured an associative priming manipulation. The observers indicated which target appeared in a search array. Unknown to them, one target appeared at the same location more often and a second target appeared in the same color more often. Both location and color biases facilitated performance, but location biases benefited the selection of all targets, whereas color biases only benefited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 55 publications
4
20
0
Order By: Relevance
“…Besides the processes of location-independent attentional selection discussed above, search performance is greatly influenced by the spatial distribution of targets and distractors in the search array. It is well-established that observers can learn to exploit uneven distributions of target locations in order to facilitate search: Targets are detected faster at locations where they appear more frequently (e.g., Anderson & Druker, 2010;Fecteau, Korjoukov, & Roelfsema, 2009;Geng & Behrmann, 2002, 2005, which Geng and Behrmann (2002) termed a target location probabilitycueing effect. Similarly, observers can learn to exploit the statistical distribution of task-irrelevant distractors to improve performance: Over time, they become better at suppressing locations where distractors appear frequently (e.g., Kelley & Yantis, 2009;Leber, Gwinn, Hong, & O'Toole, 2016;Reder, Weber, Shang, & Vanyukov, 2003).…”
Section: Role Of Dimension Weighting In the Probability Cueing Of Dismentioning
confidence: 99%
“…Besides the processes of location-independent attentional selection discussed above, search performance is greatly influenced by the spatial distribution of targets and distractors in the search array. It is well-established that observers can learn to exploit uneven distributions of target locations in order to facilitate search: Targets are detected faster at locations where they appear more frequently (e.g., Anderson & Druker, 2010;Fecteau, Korjoukov, & Roelfsema, 2009;Geng & Behrmann, 2002, 2005, which Geng and Behrmann (2002) termed a target location probabilitycueing effect. Similarly, observers can learn to exploit the statistical distribution of task-irrelevant distractors to improve performance: Over time, they become better at suppressing locations where distractors appear frequently (e.g., Kelley & Yantis, 2009;Leber, Gwinn, Hong, & O'Toole, 2016;Reder, Weber, Shang, & Vanyukov, 2003).…”
Section: Role Of Dimension Weighting In the Probability Cueing Of Dismentioning
confidence: 99%
“…Previous research has demonstrated that observers can take advantage of uneven distributions of object positions, so as to more quickly detect or discriminate objects at probable, as compared to less probable, locations (e.g., Shaw and Shaw, 1977; Geng and Behrmann, 2002, 2005; Fecteau et al, 2009; Druker and Anderson, 2010). This capability has lead to two strands of research questions: (i) is the change in performance for frequent locations due to statistical learning or to intertrial priming, and (ii), more recently, can observers learn to avoid locations which probably contain a distractor?…”
Section: Introductionmentioning
confidence: 99%
“…Second, although probability cueing effects of this kind have since been reported repeatedly within a variety of paradigms (e.g., Geng and Behrmann, 2005; Fecteau et al, 2009; Druker and Anderson, 2010), the mechanisms underlying the probability cueing effect are still subject to debate. Traditionally, probability cueing effects have been interpreted in terms of statistical learning, that is, the formation of location-specific stimulus expectancies that reflect the statistical likelihood of a target appearing at a specific location (or region) across a longer sequence of trials (e.g., Hoffmann and Kunde, 1999; Geng and Behrmann, 2002, 2005; Druker and Anderson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These data support earlier findings that colour affects longterm memory (Carriere et al 2009). It is plausible, however, that for children who may have used colour as a memory indicator the conversion of colour symbols to grey-scale is equivalent to the loss of this indication, possibly resulting in a detrimental effect on the learning process (Kasten & Navon 2008;Fecteau et al 2009). Thus, transferring grey-scale symbols to colour does not generate the same effect.…”
Section: Discussionmentioning
confidence: 99%
“…Coloured symbols have become standard features employed systematically by clinicians and therapists, mainly for enhancing symbol identification and generalisation abilities, as well as transparency and translucency (Stephenson 2009), and to provide consistency for syntax purposes and for sorting ( Wilkinson et al 2008). Extensive research has been conducted on the efficiency of combining colour in learning materials and the influence of colour on learning strategies and memory (Gegenfurtner & Rieger 2000;Smilek et al 2002;Wichmann et al 2002;Tissot & Evans 2003;Franklin et al 2008;Fecteau et al 2009). Computers have added specific qualities and ease of use, thus enabling modification of the symbols, adding colour and providing suitable graphic symbols based on the user's visual sensory profile.…”
Section: Abstract Autism Cognitive Behaviour Communication Linguismentioning
confidence: 99%